2020
DOI: 10.1002/ece3.6993
|View full text |Cite
|
Sign up to set email alerts
|

The effects of taxonomy, diet, and ecology on the microbiota of riverine macroinvertebrates

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 100 publications
(290 reference statements)
0
8
0
Order By: Relevance
“…Salmonid gills are frequently infected by A. salmonicida (Miyazaki & Kubota, 1975), and likewise are the target organ for the copepod (Kabata & Cousens, 1977). Adult females feeding on blood and tissues likely pass the bacterium to their progeny in egg sacs as there is strong evidence that terrestrial arthropods pass on microbiota to their offspring (Kwong & Moran, 2015; Sabree et al., 2012; Sabree & Moran, 2014) and very suggestive evidence that this occurs in aquatic arthropods as well (Kroetsch et al., 2020). Our separate in vivo experiments support this hypothesis, where we detected A. salmonicida in egg sacs from adult female copepods and fish infected by these copepodids in our first experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonid gills are frequently infected by A. salmonicida (Miyazaki & Kubota, 1975), and likewise are the target organ for the copepod (Kabata & Cousens, 1977). Adult females feeding on blood and tissues likely pass the bacterium to their progeny in egg sacs as there is strong evidence that terrestrial arthropods pass on microbiota to their offspring (Kwong & Moran, 2015; Sabree et al., 2012; Sabree & Moran, 2014) and very suggestive evidence that this occurs in aquatic arthropods as well (Kroetsch et al., 2020). Our separate in vivo experiments support this hypothesis, where we detected A. salmonicida in egg sacs from adult female copepods and fish infected by these copepodids in our first experiment.…”
Section: Discussionmentioning
confidence: 99%
“…environmental microbiome diversity and composition among different streams varying in quality (Atashgahi et al, 2015;Medeiros et al, 2016) and among sites along streams (Drury et al, 2013;Kroetsch et al, 2020;Wakelin et al, 2008), as well as reported differences between bacterioplankton and sediment partitions within streams (Ayayee et al, 2018;Fang et al, 2017;Hosen et al, 2017).…”
Section: Variablesmentioning
confidence: 99%
“…In studies of freshwater invertebrate gut microbiomes, there are conflicting results regarding the importance of habitat, taxonomy (family and genus), and functional feeding group (FFG) categorization in shaping gut microbial assemblages of freshwater macroinvertebrates. One study determined the taxonomy to be a more relevant determinant of gut microbiome composition of freshwater macroinvertebrates than local habitat, stream conditions, or FFG (Kroetsch et al, 2020 ). In contrast, the vast majority of the very limited studies have determined FFGs (regardless of taxonomic affiliation of samples invertebrates) to be the principal variable explaining differences in microbiome composition across freshwater macroinvertebrates (Ayayee et al, 2018 ; Kaufman et al, 2000 ; Pechal & Benbow, 2016 ; Receveur et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While microbes are among the taxa with the strongest response to engineering activities, they are rarely investigated in this context – a recent meta-analysis examined 340 studies of positive interactions in freshwater environments, finding that only 2.4% of studies considered bacteria or archaea as beneficiaries of interaction [ 33 ]. A small number of studies have evaluated the internal microbiomes of ecosystem engineering aquatic insects—for example, testing the role of feeding guild (i.e., shredder, decomposer, predator, collector/gatherer) and host identity in shaping microbiome diversity [ 34 38 ]. However, the extent to which aquatic insects shape the microbiology of the surrounding environment remains relatively unknown.…”
mentioning
confidence: 99%